2020
DOI: 10.15420/cfr.2019.11
|View full text |Cite
|
Sign up to set email alerts
|

Would You Prescribe Mobile Health Apps for Heart Failure Self-care? An Integrated Review of Commercially Available Mobile Technology for Heart Failure Patients

Abstract: Treatment of chronic diseases, such as heart failure, requires complex protocols based on early diagnosis; self-monitoring of symptoms, vital signs and physical activity; regular medication intake; and education of patients and caregivers about relevant aspects of the disease. Smartphones and mobile health applications could be very helpful in improving the efficacy of such protocols, but several barriers make it difficult to fully exploit their technological potential and produce clear clinical evidence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 19 publications
0
33
0
2
Order By: Relevance
“…Unlike MARS, this tool only assesses objective quality and has been used previously to evaluate app capabilities [ 32 , 33 ]. The functionality score consists of 7 functionality criteria and 4 functional subcategories.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike MARS, this tool only assesses objective quality and has been used previously to evaluate app capabilities [ 32 , 33 ]. The functionality score consists of 7 functionality criteria and 4 functional subcategories.…”
Section: Methodsmentioning
confidence: 99%
“…smartwatches, sensors embedded in T-shirts, socks and other clothing), automatic data collection and analysis, as well as on algorithms for detecting haemodynamic decompensation and initiating therapeutic responses in a strategy of non-intrusive monitoring. [ 2 , 3 , 12 , 14 , 32 , 33 ] Future developments will include the internet of things for continuous and imperceptible health status monitoring. [ 12 , 35 , 36 ]…”
Section: Telemedicine In Heart Failure: Remote Patient Managementmentioning
confidence: 99%
“…[ 36 ] Despite this, very few of them have been designed specifically for HF patients; a 2019 review identified 10 apps focused on HF self-care available on the Apple App Store and Google Play store. [ 37 ] Four of these were developed by scientific societies (including the American Heart Association and the Swiss Federation of Cardiology) and they were predominantly aimed at patient education, symptom tracking and prompting users to seek early care for symptoms in order to address low health literacy and poor understanding of self-care in HF patients. [ 38 , 39 ]…”
Section: Apps and Wearablesmentioning
confidence: 99%